Artificial light at night is a top predictor of bird migration stopover density - Kyle G. Horton; Jeffrey J. Buler; Sharolyn J. Anderson; Carolyn S. Burt; Amy C. Collins; Adriaan M. Dokter; Fengyi Guo; Daniel Sheldon; Monika Anna Tomaszewska; Geoffrey M. Henebry (Nature Communications, 2023)
Abstract As billions of nocturnal avian migrants traverse North America, twice a year they must contend with landscape changes driven by natural and anthropogenic forces, including the rapid growth of the artificial glow of the night sky. While airspaces facilitate migrant passage, terrestrial landscapes serve as essential areas to restore energy reserves and often act as refugia—making it critical to holistically identify stopover locations and understand drivers of use. Here, we leverage over 10 million remote sensing observations to develop seasonal contiguous United States layers of bird migrant stopover density. In over 70% of our models, we identify skyglow as a highly influential and consistently positive predictor of bird migration stopover density across the United States. This finding points to the potential of an expanding threat to avian migrants: peri-urban illuminated areas may act as ecological traps at macroscales that increase the mortality of birds during migration.